An Agile Prototyping Approach on the Design of the Purchase Request and Financial Tracking System - Buladaco, Mark Van M.; Sabugaa, Jennifer E. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose   – This paper focuses on designing a purchase request and financial tracking system to better support the government agencies in fast, easy management and better understand a more comprehensive strategy for its financial activities. Method – It employs an agile prototyping approach for fast and cost-effective turnaround. UML approach was utilized for designing process models and data models. Results – The prototypes allow you to observe real user behavior as they interact with your design and obtain detailed feedback about your designs, alternatives, and ideas before implementing them. Various process and data models are designed and presented in this paper with exact and comprehend steps for the programmers to follow during the software development life cycle (SDLC). Conclusion – Making the developed models as the government's guide in engaging and embracing emerging technological innovations would impact the purchase request processes and financial tracking management quality. These models will certainly provide new knowledge, theories, and methods for the experts who will put these prints into action or implementation and other researchers who wish to seek facts relevant to purchase requests and financial tracking of government transactions. Recommendations – It is recommended to utilize this design to develop the software in a purchase request and financial tracking in government agencies in the Philippines. It is also recommended to consider adding PR Mapping; aside from tracking the PR through status, they could suggest adding the PR mapping to track the PR, upload other documents that require in their purchase request, and adding machine learning algorithms to predict the budget allocation of each office for the next incoming years. Research Implications – This paper's results will eventually be significant in the development of a purchase request system for different government agencies in the Philippines.